Long time behaviour and self-similarity in an addition model with slow Input of monomers - Sasportes, Rafael (2015)
We consider a coagulation equation with constant coefficients and a time dependent power law input of monomers. We discuss the asymptotic behaviour of solutions as \(t → ∞\), and we prove solutions converge to a similarity profile along the non-characteristic direction.